Econometric model as an instrument for analysing structural changes in fisheries management of lakes - Marek Ramczyk (Acta Scientiarum Polonorum. Formatio Circumiectus)
The econometric model can be a precise instrument for analysing the impact of natural environment deterioration on the fishing economy. The paper presents the results of empirical studies regarding the influence of water quality changes (water pollution) in Charzykowskie Lake on the fisheries management. We have developed the economic-ecological models, which explain, from the point of view of the fisheries management, the changes of economic yield of fishing in the conditions of increased water pollution and optimum content of various substances in the water of the lake. In the empirical studies we conducted, we have analysed the impact of environmental factors on the natural structure of fish caught in Charzykowskie Lake. The empirical results show that most measures of water pollution cause changes in the structure of caught fish. Also, it can be clearly concluded that the increase in the pollution level of the lake supports the increase in proportion of the caught species that yield lower economic benefits, while it inhibits the increase in the caught volume of species that are more economically valuable. Hence the conclusion that the actions aimed at limiting the pollution of the lake will stimulate the increase in the share of species that are much more economically viable. This type of structural changes testify to a particular kind of competition between fish species having different environmental requirements, although the empirical results of econometric modelling suggest the existence of such competition also in the group of fish sharing similar needs regarding the quality of their habitat. Consequently, this situation determines the nature of the impact on the fisheries management of Charzykowskie Lake. When we take into account the changes in the structure of fish population in Charzykowskie Lake within the observed variability range of the model’s variables, there also exist neutral factors that were potentially considered to be actively impacting the changes in the caught fish structure indicators. The proposed procedures of optimisation can serve as an instrument for programming the effectiveness of fisheries management in order to maintain ecological balance.